A Study On Private Healthcare Services In Madurai District Of Tamilnadu - M. Malairaman, M. Malairaman; S. Rosita, S. Rosita (Journal of Neonatal Surgery, 2025)
Though Tamil Nadu is one of India’s highest performing states in terms of Health, Tamil Nadu Private Multi Specialty hospital service is the very important role of the health care sector. The availability of service 24 hours and 7 days and its function is very essential one of the country also. So that sector is concentrate one. But their service is very costly & most expensive one. The majority of the peoples are economically very poor family. So the minimum level of the people have use to the Private Hospitals money only we need the availability of services is we can consume true service perfectly. So the service quality of Multi Specialty is my objective. The Primary responsibility of high quality care to patients and to improve the standard of care in areas where it is deemed necessary.